Constitutive changes in pigment concentrations: implications for estimating isoprene emissions using the photochemical reflectance index. Issue 2 (23rd September 2015) - Harris, Angela; Owen, Susan Margaret; Sleep, Darren; Pereira, Maria da Glória dos Santos
Abstract : The photochemical reflectance index (PRI), through its relationship with light use efficiency (LUE) and xanthophyll cycle activity, has recently been shown to hold potential for tracking isoprene emissions from vegetation. However, both PRI and isoprene emissions can also be influenced by changes in carotenoid pigment concentrations. Xanthophyll cycle activity and changes in carotenoid concentrations operate over different timescales, but the importance of constitutive changes in pigment concentrations for accurately estimating isoprene emissions using PRI is unknown. To clarify the physiological mechanisms behind the PRI–isoprene relationship, the light environment of potted Salix viminalis (osier willow) trees was modified to induce acclimation in photosynthetic rates, phytopigments, isoprene emissions and PRI. Acclimation resulted in differences in pigment concentrations, isoprene emissions and PRI. Constitutive changes in carotenoid concentration were significantly correlated with both isoprene emissions and PRI, suggesting that the relationship between PRI and isoprene emissions is significantly influenced by constitutive pigment changes. Consequently knowledge regarding how isoprene emissions are affected by both longer term changes in total carotenoid concentrations and shorter term dynamic adjustments of LUE is required to facilitate interpretation of PRI for monitoring isoprene emissions.